Mikania Weed: A Challenge for Conservationists - Siwakoti, M (Our Nature, 2008)
The varied bioclimatic conditions of Nepal favour the introduction of different invasive alien weeds. Mikania micrantha (L.) Kunth is one of the well established invasive alien weeds in the tropical part of eastern and central Nepal. The weed has been caused serious problems in the forests, grasslands, fallow lands, croplands and wetlands of the Koshi Tappu Wildlife Reserve and its buffer zone. It kills other plants by blocking sunlight and smothering them. The Reserve has initiated to manage the weed with local community in the buffer zone. The paper attempts to highlight the problem of Mikania in the Koshi Tappu area and the efforts of community to manage the weed. Keywords: Mikania micrantha, invasive alien weed, Koshi Tappu, Nepal doi:10.3126/on.v5i1.801 Our Nature (2007)5:70-74